STUDY OF THE CURRENT RESISTANCE PATTERN TO QUINOLONES AND OTHER ANTIMICROBIALS BY MULTIDRUG RESISTANT ESCHERICHIA COLI RECOVERED FROM RETAIL CHICKEN MEAT - F. Yasin; A. A. Sheikh; M. Rabbani; A. Aslam; M. I. Rasheed; R. Tanvir (Journal of Animal and Plant Sciences, 2019)
Microbial food safety has become a worldwide public health concern. The indiscriminate use of antimicrobials in poultry had rendered bacteria resistant to multiple drugs. The dissemination of resistant genes through the food chain has probably lead to multidrug resistant strains of Escherichia coli in chicken meat. With this background in mind, the current study was conducted to ascertain the current antimicrobial susceptibility and multiple drug resistance patterns in E. coli recovered from retailed chicken meat. About 100 chicken meat samples were collected from different retail meat shops located across Lahore city. About 85 samples (85%) were found positive for E. coli. Further confirmation was done through PCR byamplifying their universal stress protein (uspA) gene. As per Kirby Bauer disk diffusion method, E. coli displayed the susceptibility towards gentamicin (86%) and ciprofloxacin (67%). The 100% resistance was observed towards chloramphenicol, colistin, tylosin each, 93% against doxycycline and 92% against ampicillin, and oxytetracycline, each. Significant resistance was observed against the quinolone group (enrofloxacine, 81.1%). All the isolates were resistant to more than 8 drugs belonging to 3 or more than 3 different classes of drugs. About 23.5% of the isolates were resistant against nine different antimicrobials and 15.3% showed resistance against eleven different drugs. The results of the in vitro susceptibility testing and multidrug resistance pattern observed in the study may provide valuable guidance to adopt good hygienic practices and curb unnecessary antimicrobial usage.
Keywords: Antibiotics; Chicken; Escherichia coli; Resistance; Retail meat